Advanced Software Engineering: Expanding the Frontiers of Software Technology IFIP 19th World Computer Congress, First International Workshop on Advanced Software Engineering, August 25, 2006, Santiago, Chile - Ochoa, Sergio F.; Roman, Gruia-Catalin.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springeronline.com. For more information about IFIP, please visit www.ifip.org.
Software Architecture -- A Meshing Tool Product Line Architecture -- A Model for Capturing and Tracing Architectural Designs -- Multidimensional Catalogs for Systematic Exploration of Component-Based Design Spaces -- Software Modeling -- Practical Verification Strategy for Refinement Conditions in UML Models -- A cognitive model of user interaction as a guideline for designing novel interfaces -- An empirical evaluation for business process tools -- Integration Ontology for Distributed Database -- Software Development Process -- SSP: A Simple Software Process for Small-Size Software Development Projects -- A Method for Collaborative Requirements Elicitation and Decision-Supported Requirements Analysis -- Defining Security Requirements Through Misuse Actions -- Experiences in Software Development -- Experiences in Portable Mobile Application Development -- Adapting Aspect-Oriented Applications: A Trial Experience -- Building a 3D Meshing Framework Using Good Software Engineering Practices.
Keywords: Software engineering; Software Engineering/Programming and Operating Systems